Radio interfaces make the difference in 3G cellular systems. - Oliphant, M.W.
Third-generation cellular telephony is on its way-not, unfortunately, as a single worldwide system, but as three incompatible ones. The main difference between the three lies in their choice of radio interface technology. This fact is crucial for several reasons, since the radio interface determines not only the fundamental capacity of a mobile radio network, but also how it deals with such issues as interference, multipath distortion, and handing off calls from one base station to another as users move around. Consequently, as might be expected, the choice of radio interface has a dramatic effect on the complexity of the system and its cost. Also, global travellers will need more than one phone with which to communicate, at least until trimode phones reach the market. To understand what is being developed, and why, the author begins with one of the stated goals of third-generation (3G) systems, namely to support variable user data rates as high as 2 Mb/s. In one way or another, all three approaches provide for adaptive bandwidth-on-demand. Two of the systems use wideband code-division multiple access (WCDMA) for the radio interface. The other uses two variations of time-division multiple access (TDMA)
Keywords: 2 Mbit/s.; 3G cellular systems; GSM; QoS; TDMA; WCDMA; Adaptive bandwidth-on-demand.; Base station; Call handoff; Interference; Mobile radio network capacity; Multipath distortion; Packet radio networks; Quality of service; Radio interfaces; System complexity; Third-generation cellular telephony; Time-division multiple access; Variable user data rates; Wideband code-division multiple access